The Administrative Data Research Network’s National Citizen’s Panel – A step towards bridging public concerns about research using administrative data.: IJPDS (2017) Issue 1, Vol 1:153, Proceedings of the IPDLN Conference (August 2016) - Knight, Judith (International Journal of Population Data Science, 2017)
ABSTRACT Background The content of administrative records are both confidential and personal, therefore the use of administrative data for research purposes is rightly and naturally of concern to us all. It is highly likely that unless public concerns can be understood, met and public confidence and support gained, that the role of research using administrative data cannot develop further. Aims As a member of the general public you may well ask, how will this research help me? The Network enables researchers across the UK to gain access to linked de-identified administrative data to benefit society i.e. research that could change health care systems, improve the distribution of funds to needier areas or has the potential to reduce crime. Method To extend the Network’s reach, the Administrative Data Research Network (ADRN) in addition to a breadth of communications and public engagement activities across the UK is developing a UK National Citizens Panel (CP). The panel will provide a representation of public views on potential changes to Network policy, procedures, governance and service provision issues. The CP will also assist with testing our public facing communications, e.g. events, website and materials. Results This paper would like to present the ADRN's case and scope for a Citizens Panel, the model adopted and its progress to date. Funded by the Economic & Social Research Council, the ADRN, set up as part of the UK Government’s Big Data initiative, is a UK-wide partnership between universities, government bodies, national statistics authorities and the wider research community.www.adrn.ac.uk.